Microvesicles Correlated with Components of Metabolic Syndrome in Men with Type 2 Diabetes Mellitus and Lowered Testosterone Levels But Were Unaltered by Testosterone Therapy - Jaco Botha; Line Velling Magnussen; Morten Hjuler Nielsen; Tine Bo Nielsen; Kurt Højlund; Marianne Skovsager Andersen; Aase Handberg (Journal of Diabetes Research)
Aims. To investigate how circulating microvesicle phenotypes correlate with insulin sensitivity, body composition, plasma lipids, and hepatic fat accumulation. We hypothesized that changes elicited by testosterone replacement therapy are reflected in levels of microvesicles. Methods. Thirty-nine type 2 diabetic males with lowered testosterone levels were assigned to either testosterone replacement therapy or placebo and evaluated at baseline and after 24 weeks. Microvesicles were analysed by flow cytometry and defined as lactadherin-binding particles within the 0.1–1.0 μm gate. Microvesicles of platelet, monocyte, and endothelial cell origin were identified by cell-specific markers and their expression of CD36 was investigated. Results. Triglycerides correlated positively with all investigated microvesicle phenotypes in this study (p<0.05), and indicators of hepatic fat accumulation, alanine aminotransferase, and gamma glutamyltransferase correlated with platelet and endothelial microvesicles and CD36-expressing microvesicles from platelets and monocytes (p<0.05). BMI, waist circumference, and fat percentage correlated with CD36-expressing monocyte microvesicles (p<0.05), while insulin sensitivity did not correlate with any microvesicle phenotypes. Microvesicle levels were unaffected by testosterone therapy. Conclusions. Metabolic syndrome components and hepatic fat accumulation correlated with microvesicle phenotypes, supporting the involvement of especially CD36 on monocytes in metabolic syndrome pathogenesis. Although testosterone therapy improved body composition measures, microvesicle phenotype levels were unaffected. This trial was registered at ClinicalTrials.gov (NCT01560546).